Fermentasi Biji Kecipir (Psophocarpus tetragonolobus) oleh Jamur Trichoderma Viride Terhadap Warna, Tekstur, dan Serat Kasar - Purwati, Catur Suci; Windyasmara, Ludfia (Fakultas Peternakan Universitas Papua, 2019)
The fermentation process is an activity of microorganisms that make products with characteristics of texture, flavor, aroma and changes in nutrient quality that better than the original raw material. It is also protein process of developing of protein from the material. This study uses a Completely Randomized Design with four treatments. P0 = Unfermented winged seeds, P1 = Winged seeds + 0,1% Trichoderma viride mushroom (Tv), P2 = Winged seeds + 0,2% Trichoderma viride mushroom (Tv), P3 = Winged seeds + 0,3% Trichoderma viride mushroom (Tv). The material used was crushed winged seeds as substrates that mixed to be homogenized. One hundred gr of each sample from every treatment was weighed, put into a perforated plastic bag (to create anaerobic atmosphere) with 2 cm thick. Subsequently, samples were incubated in fermented room at 30oC for 7 days. Each treatment was repeated 3 times. Variables observed in color, texture and coarse fiber. This study indicated that the winged fermented beans with Trichoderma viride mushroom had no effect on color, effected crude fiber and texture.